The Mucus-Binding Factor Mediates Lacticaseibacillus rhamnosus CRL1505 Adhesion but Not Immunomodulation in the Respiratory Tract - Zhou, Binghui (2024)
Lacticaseibacillus rhamnosus CRL1505 possesses immunomodulatory activities in the gastrointestinal and respiratory tracts when administered orally. Its adhesion to the intestinal mucosa does not condition its beneficial effects. The intranasal administration of L. rhamnosus CRL1505 is more effective than the oral route at modulating immunity in the respiratory tract. Nonetheless, it has not yet been established whether the adherence of the CRL1505 strain to the respiratory mucosa is needed to provide the immune benefits to the host. In this study, we evaluated the role of adhesion to the respiratory mucosa of the mucus-binding factor (mbf) knock-out L. rhamnosus CRL1505 mutant (∆mbf CRL1505) in the context of a Toll-like receptor 3 (TLR3)-triggered innate immunity response. In vitro adhesion studies in porcine bronchial epitheliocytes (PBE cells) indicated that L. rhamnosus ∆mbf CRL1505 adhered weakly compared to the wild-type strain. However, in vivo studies in mice demonstrated that the ∆mbf CRL1505 also reduced lung damage and modulated cytokine production in the respiratory tract after the activation of TLR3 to a similar extent as the wild-type strain. In addition, the mutant and the wild-type strains modulated the production of cytokines and antiviral factors by alveolar macrophages in the same way. These results suggest that the Mbf protein is partially involved in the ability of L. rhamnosus CRL1505 to adhere to the respiratory epithelium, but the protein is not necessary for the CRL1505 strain to exert its immunomodulatory beneficial effects. These findings are a step forward in the understanding of molecular interactions that mediate the beneficial effects of nasally administered probiotics.